2007
DOI: 10.1111/j.1360-0443.2007.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Is attention‐deficit/hyperactivity disorder associated with illicit substance use disorders in male adolescents? A community‐based case–control study

Abstract: Our results suggest an association between ADHD and illicit SUD in Brazilian adolescents that is not mediated by CD. These findings are potentially important from a prevention perspective because treatments are available for ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 55 publications
3
50
0
7
Order By: Relevance
“…From a genetic point of view, provided compiled evidence for common genetic networks underlying a phenotype including the externalizing disorders ADHD, CD, ODD, and substance disorder. However, a community-based case-control study found an association between ADHD and illicit substance use disorders that was not mediated by CD [10]. Yet because the sample consisted of mainly marijuana or marijuana plus cocaine users, the results might not apply to subjects with a different profile of substance abuse or disorders.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…From a genetic point of view, provided compiled evidence for common genetic networks underlying a phenotype including the externalizing disorders ADHD, CD, ODD, and substance disorder. However, a community-based case-control study found an association between ADHD and illicit substance use disorders that was not mediated by CD [10]. Yet because the sample consisted of mainly marijuana or marijuana plus cocaine users, the results might not apply to subjects with a different profile of substance abuse or disorders.…”
mentioning
confidence: 81%
“…In this context, there is still no consensus on the question whether the ADHD inattention symptoms or the ADHD hyperactivity/impulsivity symptoms are more predictive of substance problems [7][8][9]. In addition, some studies found a direct association between ADHD and substance abuse [10], while others demonstrated that this relationship disappears when cooccurring conduct disorder (CD) is taken into account [8,11,12]. Flory et al [3] noted that any observed association between ADHD and substance abuse not considering the overlap of ADHD with CD may be spurious.…”
Section: Introductionmentioning
confidence: 99%
“…For example, August et al (18) showed that only subjects with comorbid externalizing disorders (n = 82) had significantly higher rates of PSUD and regular tobacco use compared to both ADHD-only (n=27) and healthy control subjects (n=91). While some studies suggest that the increased risk for developing PSUDs that is seen in ADHD could be completely explained by comorbid CD/ODD in this group (for a review, see 19), but other studies could not confirm this (16,20).…”
mentioning
confidence: 98%
“…For instance, illicit stimulant use has been associated with psychiatric disorders, including attention-deficit/hyperactivity disorder. 37,38 Unfortunately, standardized assessment of psychiatric disorders was not undertaken as part of the At-Risk Youth Study. Similarly, there is increasing recognition of genetic factors that may predispose individuals to addictive disorders and high-risk drug use, 39 and these data were also not available in the present study.…”
Section: Limitationsmentioning
confidence: 99%